Comparison of Efficiency Principles for Welfare in Islamic and Socialist Economic Systems - Putri, Ega Seliyan; Aini, Alfithisnain Nur; Tsabitah, Nasywa Shafa; Putra, Budi Jaya (Journal of Islamic Economics and Philanthropy, 2025)
The economic theory that aspires to is an economic system that is able to create justice and common prosperity, accompanied by the concept of the blessings of the world and the hereafter. This is the theory of Islamic economics that will bring justice and comprehensive prosperity. Islamic economics is considered a solution to overcome contemporary economic problems. The source of thought of the Islamic economic system is the Islamic creed and ideology which is based on the Qur'an and as-Sunnah. With this foundation, Islamic economics is distinctive, unique and different from socialist or communist economic systems. The Islamic economic system is an independent economic system and is independent of other economic systems. What distinguishes the Islamic economic system from other economic systems is that the principles of Islamic economics in the application of the principle of efficiency still maintain the preservation of the natural environment. The economic motive of Islam is to seek luck in this world and in the hereafter like the caliph with the way of worship in a broad sense. Islam recognizes the welfare of individuals and the social welfare of society that complement each other, not compete and contradict each other.